2015
DOI: 10.3389/fnhum.2015.00365
|View full text |Cite
|
Sign up to set email alerts
|

“Brain MR spectroscopy in autism spectrum disorder—the GABA excitatory/inhibitory imbalance theory revisited”

Abstract: Magnetic resonance spectroscopy (MRS) from voxels placed in the left anterior cingulate cortex (ACC) was measured from 14 boys with Autism Spectrum Disorder (ASD) and 24 gender and age-matched typically developing (TD) control group. Our main aims were to compare the concentration of γ-aminobutyric acid (GABA) between the two groups, and to investigate the relationship between brain metabolites and autism symptom severity in the ASD group. We did find a significant negative correlation in the ASD group between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 66 publications
8
53
0
Order By: Relevance
“…Specifically, higher SRS‐2 scores (indicative of greater ASD symptomatology) were associated with reduced concentrations of GABA+ in the VIS. This finding is consistent with previous findings linking reductions in GABA to increases in ASD symptoms [Brix et al, ; Carvalho Pereira et al, ]. However, in light of the inverse relationship between VIS GABA+ and VST performance, this result appears to be conflicting, especially given that prior reports have shown that faster, more efficient search is related to ASD symptom severity [Joseph et al, ; Keehn et al, ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, higher SRS‐2 scores (indicative of greater ASD symptomatology) were associated with reduced concentrations of GABA+ in the VIS. This finding is consistent with previous findings linking reductions in GABA to increases in ASD symptoms [Brix et al, ; Carvalho Pereira et al, ]. However, in light of the inverse relationship between VIS GABA+ and VST performance, this result appears to be conflicting, especially given that prior reports have shown that faster, more efficient search is related to ASD symptom severity [Joseph et al, ; Keehn et al, ].…”
Section: Discussionsupporting
confidence: 89%
“…Finally, VIS was chosen to determine whether superior search in ASD is associated with enhanced discrimination [O'Riordan & Plaisted, ], as occipital GABA levels are associated with orientation perceptual thresholds [Edden et al, ; Song et al, ]. Finally, because others have hypothesized that an E/I imbalance may contribute to the development of ASD [Hussman, ; Rubenstein & Merzenich, ], and prior findings have shown an association between GABA and ASD symptom severity [Brix et al, ; Carvalho Pereira, Violante, Mouga, Oliveira, & Castelo‐Branco, ] we examined the relationship between GABA levels and measures of ASD symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous non-invasive 1 H-MRS studies reported increased cerebral concentrations of Glu in Heschl’s gyrus and the anterior cingulate cortex (Brown et al, 2013; Joshi et al, 2013). Moreover, decreased concentrations of GABA in anterior cingulate cortex, motor and auditory cortex, frontal lobe and Heschl’s gyrus (Cochran et al, 2015; Gaetz et al, 2014; Harada et al, 2011; Kubas et al, 2012; Rojas et al, 2014) are reported, supporting that an imbalanced E/I system exists in individuals with ASD (Brix et al, 2015). …”
Section: Introductionmentioning
confidence: 83%
“…The balance of the excitatory and inhibitory impulses may determine the GABAergic cell activity [18,41]. Correlation between GABA and glutamate layers in prefrontal cortices [41] might be an indicator of the relationship between excitatory and inhibitory neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between GABA and glutamate layers in prefrontal cortices [41] might be an indicator of the relationship between excitatory and inhibitory neurotransmission. Since the excitatory neurotransmission is degraded in neurodevelopmental disorders, activity of the GABAergic cells and GABA levels might be altered in order to protect the balance between excitatory and inhibitory neurotransmission [41-43]. …”
Section: Discussionmentioning
confidence: 99%